An adaptive and safe ubicomp for HPC applications. (24th September 2009) - Shi, Xuanhua; Pazat, Jean-Louis
This paper presents an adaptive component-based infrastructure, which is composed with two parts, the mobile devices and the grid infrastructure. Because of the distributed, dynamic, and large-scale features, the ubiquitous computing (ubicomp) is vulnerable to malicious attacks for HPC applications. This paper presents an adaptive component at the grid infrastructure side to target the safety problems; the adaptive component makes adaptive replication actions according to different kinds of safety situations. This paper also presents the evaluation for the adaptive actions, which show that the adaptive method can handle the safety problems for HPC applications in ubicomp.